-10=4x-6x-10

Simple and best practice solution for -10=4x-6x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=4x-6x-10 equation:


Simplifying
-10 = 4x + -6x + -10

Reorder the terms:
-10 = -10 + 4x + -6x

Combine like terms: 4x + -6x = -2x
-10 = -10 + -2x

Add '10' to each side of the equation.
-10 + 10 = -10 + 10 + -2x

Combine like terms: -10 + 10 = 0
0 = -10 + 10 + -2x

Combine like terms: -10 + 10 = 0
0 = 0 + -2x
0 = -2x

Solving
0 = -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
0 + 2x = -2x + 2x
Remove the zero:
2x = -2x + 2x

Combine like terms: -2x + 2x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| -36*-14= | | -38-10x=36-17x | | 4z-8=3z-1 | | 8(k-2)=9k+1 | | 2x+4y=-32 | | -24n+24+2n= | | -6a+4=a+9-2a | | 7x-4(x-6)=2(x-8) | | 3j-2j+8=2j+1 | | 4-10x/25=185 | | X-32+4=12 | | 4x+8-6= | | 7-1/4(8p-8)-5p | | n/9+7=10 | | -2x-8=-12 | | 0.5(2-4w)=2w-9 | | 3X-y+8=0 | | 7-7x=-6 | | 0.5(2-4a)=2w-9 | | 18=-6x+x-2 | | (x-5)/10+(1+2x)/5=(3-x)/4 | | 40*2=110/1,5 | | 2m+4m-3=9 | | -x/12=-1 | | x+6=34*1.5 | | 5x^2+25x+20= | | -68=x+7x+4 | | 3x-2=34*2 | | 11(x-2)=6x+13 | | 3(x+1)+37=-2x | | x+x+6+3x=86 | | 9x+7=5x+11 |

Equations solver categories